I see Allah everywhere - Khan,Saniyasnain (Goodword kidz: New Dehli, 2010)
The book uses simple text and vibrant illustrations to depict various aspects of nature$1 (Bsuch as the sky, trees, and animals$1 (Bhighlighting that these creations are signs of Allah's presence and power. It encourages children to recognize and appreciate the beauty and order in the world around them, fostering a sense of awe and gratitude towards the Creator.s